The substitution process of heavy fuel oil with natural gas in the industrial sector of Valle del Cauca and Cauca – Colombia 2004-2012 - Rangel Jiménez, Andrés Eduardo; Portilla Salazar, Carlos Johnny (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The main purpose of this paper is to analyze the substitution process from heavy fuel oil to natural gas by medium-sized and large companies located in Valle del Cauca and the north of Cauca in the period 2004–2012. Likewise, using a random effects Probit model in Panel, the propensity of these industries to substitute highly polluting fuel with natural gas is estimated. The results show that the difference in cost between natural gas and other fuels is a determinant of the probability of replacement. In addition, it is confirmed that the industries with a lower likelihood of carrying out this replacement are those that use coal in their production processes.